2010
DOI: 10.1007/s12230-010-9145-4
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Broad-Sense Heritability of Mineral Content in Potato: Iron

Abstract: Iron deficiency in humans occurs in all regions of the world. Potatoes are a modest source of iron. The purpose of this study was to determine if genetic variation for potato tuber iron content exists. Iron content in unpeeled potato was measured in 33 clones, including varieties and advanced breeding selections, in three trials (Tri-State, Western Regional Russet, Western Specialty/Red) which in total were grown in twelve environments. In two trials significant genotype × environment interaction occurred. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 22 publications
5
27
2
1
Order By: Relevance
“…The rankings of the cultivars according to the tuber concentrations of the two minerals were identical indicating a positive correlation between the genotypic concentrations of the two minerals, which was also found in previous work with native Andean potatoes in Peru (Burgos et al 2007) and in other studies with potato (Carli and Khalikov 2008;Brown et al 2010;Lefèvre et al 2012). The ranking of the cultivars was maintained at all sites and following Fe and Zn fertilizer applications (Table 6).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The rankings of the cultivars according to the tuber concentrations of the two minerals were identical indicating a positive correlation between the genotypic concentrations of the two minerals, which was also found in previous work with native Andean potatoes in Peru (Burgos et al 2007) and in other studies with potato (Carli and Khalikov 2008;Brown et al 2010;Lefèvre et al 2012). The ranking of the cultivars was maintained at all sites and following Fe and Zn fertilizer applications (Table 6).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown similar strong site effects on tuber mineral concentrations (Burgos et al 2007;Brown et al 2010;Haynes et al 2012;Nassar et al 2012). Burgos et al (2007) reported a variation in tuber Fe concentration in the 3-fold range among sites in Peru, whereas Brown et al (2010) reported a 4-fold difference in Fe tuber concentrations among sites in the United States.…”
Section: −1mentioning
confidence: 65%
See 1 more Smart Citation
“…In a previous publication (Brown et al 2010) the iron content of the genotypes in these trials was reported. The correlation of iron and zinc was positive and highly significant in the Regional Red/Specialty Trial (r=0.84, P<0.01), not significant in the Regional Russet Trial and highly significantly negatively correlated in the Tri-State Trial (r=−0.70, P<0.01).…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that breeding for high tuber Ca, Fe and Zn concentrations might have potential. Furthermore, the heritability of tuber mineral concentrations in potato were found to be moderately high (Brown et al 2010(Brown et al , 2011(Brown et al , 2012(Brown et al , 2013(Brown et al and 2014Haynes et al 2012;Paget et al 2014;Zorrilla et al 2014), indicating the possibility of mineral biofortification by plant breeding.…”
Section: Discussionmentioning
confidence: 99%